Digital Resistance to Social Media Taxation: A Semiotic Analysis of Protest Discourse on Platform X - Irwanto, Irwanto; Hariatiningsih, Laurensia Retno; Yunita, Ria; Irhamdhika, Gema; Bender, George Wilhelm (Communication, 2026)
This study examines netizen resistance to Indonesia's proposed 2026 social media tax policy. It employs a qualitative analysis of interactions on Platform X. This research employs van Leeuwen's (2015) social semiotics and W. Lance Bennett and Alexandra Segerberg's (2015) connective action theory, in analyzing how users construct collective resistance narratives. These narratives emerge through multimodal signs and personalized participation. Data from influential accounts, including @kompascom, @detikcom, and individual netizens, reveal three key resistance patterns. First, users construct injustice narratives using words like "targeting" and surveillance icons. Second, digital interactions connect personal frames to collective action through sarcasm and metaphors. Third, multimodal compositions such as infographics, binary signs, and temporal strategies enhance narrative coherence. The findings indicate that netizens frame the tax policy as both an economic burden and a mechanism of social control, articulating fear of privacy violations and systemic injustice. The integration of semiotic analysis with connective action theory reveals how platform affordances facilitate resistance without a hierarchical organization. This transformation positions X as a digital public sphere for political contestation. This research contributes to the understanding of contemporary digital resistance in Global South contexts. It highlights how algorithmic amplification and multimodal communication shape the perceptions of policy legitimacy in Indonesia's evolving digital democracy. The study also underscores the need for more transparent policy communication. Finally, it provides a theoretical framework for analyzing digital protest in post-authoritarian societies. Keywords: Digital Resistance, Social Media Tax Policy, Connective Action, Social Semiotics, Platform